A fructose/H+ symporter controlled by a LacI-type regulator promotes survival of pandemic Vibrio cholerae in seawater - Yutao Liu (Nature Portfolio, 2021)
The bacterium Vibrio cholerae can colonize the human intestine and cause cholera, but spends much of its life cycle in seawater. Here, Liu et al. identify a fructose uptake system that is important for the growth of the bacteria in seawater, where fructose concentrations are low.